2002
DOI: 10.1104/pp.128.2.472
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Seedling Growth, Storage Lipid Mobilization, and Photosynthetic Gene Expression Are Regulated by Carbon:Nitrogen Availability

Abstract: The objective of the current work was to establish the degree to which the effects of carbon and nitrogen availability on Arabidopsis seedling growth and development are due to these nutrients acting independently or together. Growth of seedlings on low (0.1 mM) nitrogen results in a significant reduction of seedling and cotyledon size, fresh weight, chlorophyll, and anthocyanin content but a slight increase in endogenous sugars. The addition of 100 mM sucrose (Suc) to the nitrogen-depleted growth media result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(160 citation statements)
references
References 0 publications
7
151
2
Order By: Relevance
“…Oil drops in seedlings often correlate with the inhibition of stored lipid breakdown. A previous study showed that simultaneously decreasing N concentration and adding exogenous sugar resulted in 80% of eicosenoic acid, a 20:1 fatty acid that is specific to seed oil, being maintained 6 d after germination, suggesting delayed degradation of storage oil (Martin et al, 2002). However, we found that genes involved in TAG biosynthesis and accumulation were increased when the N concentration was reduced from 60 to 0.1 mM.…”
Section: There Is a Homeostasis Between Tag Biosynthesis And Degradatcontrasting
confidence: 45%
See 2 more Smart Citations
“…Oil drops in seedlings often correlate with the inhibition of stored lipid breakdown. A previous study showed that simultaneously decreasing N concentration and adding exogenous sugar resulted in 80% of eicosenoic acid, a 20:1 fatty acid that is specific to seed oil, being maintained 6 d after germination, suggesting delayed degradation of storage oil (Martin et al, 2002). However, we found that genes involved in TAG biosynthesis and accumulation were increased when the N concentration was reduced from 60 to 0.1 mM.…”
Section: There Is a Homeostasis Between Tag Biosynthesis And Degradatcontrasting
confidence: 45%
“…Arabidopsis (Arabidopsis thaliana) seeds were sterilized and plated on MS medium with different concentrations of N and Suc as described by Martin et al (2002). The molar ratio of KNO 3 to NH 4 NO 3 was maintained in each medium as MS medium described by Murashige and Skoog (1962).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, external application of Suc or Glc results in a decreased level of chlorophyll a/b-binding protein mRNA (Martin et al, 2002;Moore et al, 2003). In contrast, we observed no change in the expression of CAB21 mRNA between ethylene-sensitive and insensitive plants (Fig.…”
Section: Ethylene-insensitive Plants Have Reduced Photosynthetic Capamentioning
confidence: 65%
“…The sample was extracted with 1 mL of chloroform and centrifuged at 13,000 rpm for 5 min (Nemie-Feyissa et al, 2014). Anthocyanins were measured in the aqueous upper phase at 530 nm (modified from Martin et al, 2002).…”
Section: Phytochemical Extraction and Assaysmentioning
confidence: 99%